A null allele of Dnaaf2 displays embryonic lethality and mimics human ciliary dyskinesia. (20th May 2019) - Cheong, Agnes; Degani, Rinat; Tremblay, Kimberly D; Mager, Jesse
Abstract: The dynein axonemal assembly factor (Dnaaf) protein family is involved in preassembly and stability of dynein arms before they are transported into the cilia. In humans, mutations in DNAAF genes lead to several diseases related to cilia defects such as primary ciliary dyskinesia (PCD; OMIM: 612518). Patients with PCD experience malfunctions in cilia motility, which can result in inflammation and infection of the respiratory tract among other defects. Previous studies have identified that a mutation in DNAAF2 results in PCD and that 40% of these patients also experience laterality defects. In an outbred genetic background, Dnaaf2 homozygotes die after birth and have left/right defects among other phenotypes. Here we characterize a novel null allele of Dnaaf2 obtained from the International Mouse Phenotyping Consortium. Our data indicate that on a defined C57bl/6NJ genetic background, homozygous Dnaaf2 mouse embryos fail to progress beyond organogenesis stages with many abnormalities including left–right patterning defects. These findings support studies indicating that hypomorphic mutations of human DNAAF2 can result in ciliary dyskinesia and identify Dnaaf2 as an essential component of cilia function in vivo .